A Lot Done but Much More to Do: An Assessment of the Cuban Economic Transformation So Far. (1st July 2013) - ,
Abstract : The aim of this paper is to provide a brief summary of the last two years of the process of transformation in Cuba from a primarily economic perspective. It consists of five parts: an introduction, which makes it clear that the changes are not merely economic; a first section that deals with the urgent needs of economic development; a second section that seeks to highlight how the process has been gaining in depth and scope and now focuses more on how to define the paths of development than on survival; a third section that evaluates the results in two perspectives, from the dynamics of the process of change and from the country's economic performance in recent years (although with restrictions due to data availability); and conclusions.